Elastic lateral-torsional buckling analysis of plane frames - Uzzaman, A. T. M. Khalid; Usami, Tsutomu; The Australian Government (Bangkok : Asian Institute of Technology, 1977)
A general formulation for the elastic lateral-torsional buckling of plane frames is presented with the use of finite element technique. The effects of in-plane deformations on the lateral-torsional buckling are included in the present analysis. Unlike the most of the previous studies using the similar approach, in-plane and out-of-plane (lateral-torsional) analyses are treated separately to reduce the computational efforts. Numerical examples are shown for some beams, beam-columns and portal frames.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1977
Keywords: Structural frames